A Schulman partners with 3M to develop insulating and reduced weight solutions. Issue 4 (April 2018) - Unknown
Abstract : US materials firms A. Schulman, Inc and 3M Co are collaborating to develop insulation and weight-reduced compounds that incorporate 3M™ Glass Bubbles. Combining these engineered hollow glass microspheres with filler systems from A. Schulman can achieve a weight reduction of 15% without compromising on product properties, the companies report. The partnership is focusing on western Europe and especially the predominantly German-speaking DACH region.